A Prognostic Decision Model for Offshore Wind Turbines Maintenance. Issue 5 (October 2015) - Sinha, Yashwant; Steel, John A
Frequent unscheduled random maintenance activities have significantly increased the operating cost of Offshore Wind Turbines (OWT). These activities account for ∼65% of the overall OWT maintenance costs or 23% of the lifetime costs of OWT, equivalent to ∼ £26 M/yr for a 100MW offshore wind farm. This work performs a quantitative evaluation of the maintenance model suggested by Sinha Y et al. (2013) as a means to determine the threshold levels for planning an economical but effective maintenance for OWT. This study suggests that the model put forward provides a comprehensive framework to make maintenance decisions for OWT components by questioning their Availability, Reliability, Safety, Productivity and Availability of Upgrade Technology. Some case studies have been discussed towards the end of this work that validates this model and brings financial benefits. It is expected that practical use of the maintenance decision model, along with relationships developed in this work, would result in planning for economical, effective and efficient OWT maintenance.